2003
DOI: 10.1002/jbm.b.10068
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to wear debris generated in carbon based composites as potential bearing surfaces for artificial hip joints

Abstract: UHMWPE wear particles have been implicated in osteolysis, implant loosening, and long-term failure of total hip arthroplasties in vivo. This study examined four carbon-based composite materials as alternatives for UHMWPE in joint bearings. These materials were HMU-CVD, SMS-CVD, P25-CVD, and CFR-PEEK. New bearing materials should satisfy certain criteria: they should have good wear properties that at least match UHMWPE, and produce wear particles with low levels of biological activity. Of the four materials tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 22 publications
0
62
0
2
Order By: Relevance
“…As part of a larger study on composite candidate biomaterials, Howling and coworkers [177] investigated the bioactivity of wear debris generated by a 30% PAN CFR-PEEK composite pins articulating against alumina plates in a bidirectional pin-on-disk tester. The wear particles were extracted from the test fluid and exposed to L929 and U937 cells in an in vitro culture model to evaluate their effect on cellular viability.…”
Section: Arthroplasty Bearing Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a larger study on composite candidate biomaterials, Howling and coworkers [177] investigated the bioactivity of wear debris generated by a 30% PAN CFR-PEEK composite pins articulating against alumina plates in a bidirectional pin-on-disk tester. The wear particles were extracted from the test fluid and exposed to L929 and U937 cells in an in vitro culture model to evaluate their effect on cellular viability.…”
Section: Arthroplasty Bearing Surfacesmentioning
confidence: 99%
“…These basic studies established that the friction and wear behavior of PEEK depended not only upon the type and amount of fiber reinforcement, but also the surface roughness of the PEEK surface and the counterface, as well as temperature, sliding speed, and contact pressure. Although an extensive body of tribological literature exists for PEEK and its composites, when we restrict ourselves to conditions relevant to total joint replacement applications, only a limited number of investigations have been reported in the peer-reviewed literature [17,[176][177][178][179].…”
Section: Arthroplasty Bearing Surfacesmentioning
confidence: 99%
“…Considering the results of the wear particle analysis, we expect the biological response of the PMPC-grafted PEEK and CFR-PEEK cups in vivo to be comparable with those of PE or CLPE [12,35]. This is supported by the cell culture experiments performed by Howling et al, who reported that CFR-PEEK wear particles had no cytotoxic effects and could not possibly cause adverse cellular (L929 and U937 cells) reactions [36]. Jones et al reported that wear particles of CFR-PEEK cups exhibited no cytotoxic or mutagenic potential in the Ames test and the evaluation of chromosome aberration in human lymphocytes [12].…”
Section: Discussionmentioning
confidence: 61%
“…Goodman proposed that the immune response to polymer particles is non-specific and macrophage mediated via the production of cytokines [31]. It is widely agreed that UHMWPE wear particles in the size range 0.1 to 1.0 m have been shown to be the most biological reactive [11,32]. Moreover, quantity, composition, and shape of the wear particles all play important roles in determining the host tissue response [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quantity, composition, and shape of the wear particles all play important roles in determining the host tissue response [33]. There are plenty of studies [32][33][34] that report on the biocompatibility of PEEK wear debris, however none focus on wear debris generated in cervical TDA. A recent in-vitro wear study pointed out that the wear particle size distribution of a PEEK-on-PEEK cervical disc was from 0.23 to 0.51 m with a mean roundness of 0.5 [30].…”
Section: Discussionmentioning
confidence: 99%